ANALISIS PENDAPATAN USAHA TAHU BULAT DI KELURAHAN TERUKIS RAHAYU KECAMATAN MARTAPURA KABUPATEN OKU TIMUR - Andri Irawan, Zainul Adhar, Leni Sabrina, Iman Sulaiman (JASEP, 2025)
Tofu is a healthy soybean-based food ingredient that has been consumed by Asian people for thousands of years. This study aims to analyze the revenue of the round tofu business. The study was conducted in Terukis Rahayu Village, Martapura District, East OKU Regency, using a case study method. The results show that the round tofu business revenue is obtained from the difference between the amount of revenue and total production costs in one month, which is IDR 19,893,691.00/month with an average revenue of IDR 663,123.00/day.